Traducendo Brecht. Il carteggio tra Cesare Cases e Gabriele Mucchi (1985-1994) - Martini, Magda (L'ospite ingrato, 2024)
The correspondence between Cesare Cases and the artist Gabriele Mucchi bears witness to a genuine confrontation on several fronts between two great 20th century Italian intellectuals. The occasion for the epistolary exchange, in the mid-1980s, was a close collaboration for the publication of a collection of Brecht’s poems chosen and translated by Mucchi, for which Cases wrote the preface. But the confrontation on topics such as metrics, poetics and politics laid the foundations for a sincere mutual esteem and the birth of an ironic friendship. Although in their differing moods, Cases and Mucchi at last found themselves commenting on the fall of the Berlin Wall and the transformations this brought about in the German Democratic Republic and in the Italian political and intellectual scene.